KAUSALITAS JUMLAH PENDUDUK, KONSUMSI RUMAH TANGGA, URBANISASI DAN KESEJAHTERAAN MASYARAKAT INDONESIA - Salsabila Nurul Aini; Lucia Rita Indrawati (Transpublika Publisher, 2022)
The Preamble to Indonesia's 1945 Constitution declares unequivocally that the state was established to protect the whole Indonesian population, advance the public welfare, and educate the nation's citizens. The government has implemented a number of development programs with the primary goal of promoting community welfare. Nevertheless, efforts to quantify welfare continue to be a subject of study for economists. In recent years, definitions and methodologies for evaluating welfare in economic development have continued to evolve. This study examines the relationship between population, household consumption, urbanization, and community welfare, as assessed by Indonesia's per capita GDP from 1990 to 2019. This investigation use the Vector Error Correction Model (VECM) technique. According to the findings of the estimation, the variables population (JP) [-3.05594] and household consumption (KRT) [-5.17939] have a meaningful effect on people's welfare (GDP per Capita), whereas urbanization (URB) has no influence.